2021
DOI: 10.1002/adma.202170286
|View full text |Cite
|
Sign up to set email alerts
|

Production of Multiple Cell‐Laden Microtissue Spheroids with a Biomimetic Hepatic‐Lobule‐Like Structure (Adv. Mater. 36/2021)

Abstract: Biomedical Applications In article number 2102624, Songwan Jin and co‐workers generate liver spheroids that resemble the in vivo structure of the lobules. The structural integrity is maintained for several days, engendering an increased performance of cellular function. This is achieved thanks to the combination of two cutting edge technologies: preset‐extrusion 3D bioprinting and microfluidics. Moreover, structured microtissues once injected into animals show a better engraftment, bringing to light the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The methodical allocation and complete encapsulation of the parenchymal section by ECs may contribute to the preservation of the morphology of structured hepatocyte spheroids, in addition, the layered structure also mimicked the hepatic lobule architecture in the actual liver. [ 30 ] In addition, after 3 days of culture, CD31 expression was evident around the HUVEC‐covered hepatocyte spheroids (Figure 3m), whereas CD31 was not detected in the hepatocyte spheroids alone (Figure 3i). A previous report has indicated that VEGF stimulates the migration and induces an increase in paracellular permeability of HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…The methodical allocation and complete encapsulation of the parenchymal section by ECs may contribute to the preservation of the morphology of structured hepatocyte spheroids, in addition, the layered structure also mimicked the hepatic lobule architecture in the actual liver. [ 30 ] In addition, after 3 days of culture, CD31 expression was evident around the HUVEC‐covered hepatocyte spheroids (Figure 3m), whereas CD31 was not detected in the hepatocyte spheroids alone (Figure 3i). A previous report has indicated that VEGF stimulates the migration and induces an increase in paracellular permeability of HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Indeed, the application of the angiogenesis-on-achip platform can provide opportunities to investigate the effects of fluid shear stress or growth factors on the processes involved in vascular morphogenesis. 30 Nevertheless, although these platforms provide vital biomimetic models to reconstitute angiogenic sprouting morphogenesis in vitro, we are still unable to fully describe and scale up a multilayer blood structure in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Cell‐laden bioprinting enables rapid production of customized implants containing highly dense and precisely arranged cells. [ 16–19 ] But cells enclosed within bioinks face risks of compromised viability, activity and DNA stability from unavoidable mechanical stress and free radical during printing and molding, particularly for delicate cell types like stem cells and neuronal cells. [ 20–23 ] Overcoming this challenge is critical to enable translational applications.…”
Section: Introductionmentioning
confidence: 99%